Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Loyalitas Pelanggan yang di Mediasi oleh Kepuasan Pelanggan Richeese Factory di Kota Cimahi - Pahrurozi, Atep; Nurtjahjadi, Edi (J-MAS (Jurnal Manajemen dan Sains), 2024)
One type of restaurant that is growing in Indonesia is fast food restaurants, which are even more popular with all groups because they are able to meet the needs of pe ople who have limited time (Riadi, 2021). According to (Apkrindo) estimates that in Indonesia fast food restaurants will continue to grow in the second quarter of 2023 (Prasetyo, 2023). However, one of the Richeese Factory fast food restaurants experienced an average decrease in 2021-2023 of 1.1%. This indicates that there is a decrease in Richeese Factory customer loyalty in Cimahi city. The purpose of this study was to determine the effect of product quality and service quality on customer loyalty mediated by Richeese Factory customer satisfaction in Cimahi city. The number of samples I used was 120 respondents with convenience sampling technique. The data sources for this study were collected through distributing questionnaires that were valid and reliable and had passed the classical assumption test, to test the hypothesis in this study using multiple regression tests and sobel tests. SPSS version 26 software is used for testing tools. The results of this research are that product quality has a positive effect on customer satisfaction, service quality has a positive effect on customer satisfaction, customer satisfaction has a positive effect on customer loyalty and customer satisfaction play a role in mediating the effect of product quality and service quality on customer loyalty.